Different distribution of neuromedin S and its mRNA in the rat brain: NMS peptide is present not only in the hypothalamus as the mRNA, but also in the brainstem - Mori, Miwa; Mori, Kenji; Ida, Takanori; Sato, Takahiro; Kojima, Masayasu; Miyazato, Mikiya; Kangawa, Kenji (Frontiers in Endocrinology, 2012)
Neuromedin S (NMS) is a neuropeptide identified as another endogenous ligand for two orphan G protein-coupled receptors, FM-3/GPR66 and FM-4/TGR-1, which have also been identified as types 1 and 2 receptors for neuromedin U structurally related to NMS. Although expression of NMS mRNA is found mainly in the brain, spleen, and testis, the distribution of its peptide has not yet been investigated. Using a newly prepared antiserum, we developed a highly sensitive radioimmunoassay for rat NMS. NMS peptide was clearly detected in the rat brain at a concentration of 68.3 ± 3.4 fmol/g wet weight, but it was hardly detected in the spleen and testis. A high content of NMS peptide was found in the hypothalamus, midbrain, and pons–medulla oblongata, whereas abundant expression of NMS mRNA was detected only in the hypothalamus. These differing distributions of the mRNA and peptide suggest that nerve fibers originating from hypothalamic NMS neurons project into the midbrain, pons, or medulla oblongata. In addition, abundant expression of type 2 receptor mRNA was detected not only in the hypothalamus, but also in the midbrain and pons–medulla oblongata. These results suggest novel, unknown physiological roles of NMS within the brainstem.